Síntese, preparação e caracterização de fotocatalisadores a base de TiO2 imobilizados em vidro borosilicato - Ludwichk, Raquel (2014)
This study focused on evaluating the obtaining and characterization of TiO2-based photocatalysts immobilized on borosilicate glass. The synthesis of semiconductor was performed according to the sol-gel method, based on a multivariate design factorial design of experiments, to evaluate the effects of experimental variables of interest on the microstructure, adhesion and photocatalytic activity of the material, for which the blue QR-19 reactive dye and the effluent from the explosives industry, red water, were used as model substrates. Among the variables studied, the addition of silver (Ag), polyethylene glycol (PEG) and hydrogen peroxide (H2O2), it was observed that only the addition of silver and H2O2 resulted in significant effect on the influence of the studied responses. After obtaining samples of borosilicate glass-TiO2-Ag second optimized conditions, they were characterized by scanning (SEM) electron microscopy associated with energy dispersive spectrometer (EDS) and infrared spectroscopy with Fourier transformed (FTIR). Microstructure characterization tests performed by SEM showed a good distribution and uniformity of material while techniques EDS and FTIR confirmed the presence in the samples of the elements silver, titanium and oxygen as well as frequencies of typical absorption at 600 cm -1 assigned connecting O-Ti-O. A kinetic study to evaluate on a larger time interval the photocatalytic activity of the material borosilicate glass-TiO2-Ag, and its efficiency for the degradation of chemical constituents nitroaromáticas species of an effluent of nitroaromatic explosives industry, showed the conditions of study a reduction of chemical oxygen demand (COD) of 32%, reduction of phenols 52% and greater than 98% discoloration, with complete degradation of nitroaromatic compounds identified by gas chromatography coupled to mass spectrometry.